α-Mangostin and lawsone methyl ether in tooth gel synergistically increase its antimicrobial and antibiofilm formation effects in vitro - Wipawee Nittayananta; Panjaporn Wongwitthayakool; Teerapol Srichana; Chadaporn Setthanurakkul; Panthakarn Yampuen; Paphawarin Terachinda; Titima Deebunjerd; Jiratchaya Tachapiriyakun (BMC, 2023)
Abstract Objectives α-Mangostin (α-MG) and lawsone methyl ether (LME) show antimicrobial and anti-biofilm activities. The objectives of this study were to develop a herbal tooth gel containing α-MG and LME plus fluoride and determine its antimicrobial, anti-biofilm formation, anti-cancer, anti-inflammatory, wound healing, and enamel microhardness effects. Methods Antimicrobial assays against Streptococcus mutans, Porphyromonas gingivalis, and Candida albicans were performed. The microbes' ultrastructural morphology was assessed using Transmission Electron Microscopy. The effect on microbial biofilm formation was tested by a broth microdilution. Cell viability was assessed with MTT assay. The anti-inflammatory effect was investigated by measuring inhibition of nitric oxide production. Enamel microhardness was measured via Vickers microhardness testing. The enamel chemical composition was investigated with Fourier Transform Spectrometer. The enamel surface morphology and fluoride content were examined by Scanning Electron Microscopy and Energy Dispersive X-ray Spectroscopy. Results The results show synergistic effects of α-MG and LME on antimicrobial activity and antibiofilm formation without cytotoxicity at a therapeutic dose. At a higher dose, the tooth gel inhibited proliferation of cancer cell line. Enamel microhardness was increased after brushing with the tooth gel plus fluoride. A large amount of fluoride was detected on the enamel surface. Conclusion The tooth gel containing α-MG and LME synergized its antimicrobial activity and antibiofilm formation and inhibited oral cancer cell proliferation. Incorporating fluoride into the tooth gel increased enamel microhardness. Thus, the herbal tooth gel containing α-MG and LME plus fluoride may be useful for preventing dental caries and promoting oral health.